2023
DOI: 10.47391/jpma.6976
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of congenital inner ear malformations among cochlear implant candidates at a tertiary care hospital Pakistan

Abstract: Objectives: To determine the frequency and factors associated with inner ear anomalies among cochlear implant candidates. Method: The cross-sectional study was conducted at the Department of Otolaryngology, Aga Khan University Hospital, Karachi, from October 2021 to March 2022, and comprised patients of either gender aged <18 years who received cochlear implants. All subjects underwent computed tomography and magnetic resonance imaging of the temporal bone to identify any inner ear anomaly. The data gathere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The results are comparable to other studies conducted in Pakistan and other countries which showed highest prevalence of CNS defects. 11,12 In this study, the most frequent neurological anomalies were hydrocephaly and spina bifida followed by Down syndrome, while most The reason of the high prevalence of neural tube defects, i.e., spina bifida and associated hydrocephaly could be a lack of maternal folic acid use during the period of conception and early development. 16 Down syndrome is caused by trisomy of chromosome 21 and associated with the advance age of mother.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The results are comparable to other studies conducted in Pakistan and other countries which showed highest prevalence of CNS defects. 11,12 In this study, the most frequent neurological anomalies were hydrocephaly and spina bifida followed by Down syndrome, while most The reason of the high prevalence of neural tube defects, i.e., spina bifida and associated hydrocephaly could be a lack of maternal folic acid use during the period of conception and early development. 16 Down syndrome is caused by trisomy of chromosome 21 and associated with the advance age of mother.…”
Section: Discussionmentioning
confidence: 61%
“…The authors remarked that CNS were the most frequently affected system and CA were not uncommon in our society. 11 Another descriptive cross-sectional study was conducted at Mardan Medical Complex, Mardan, and infants with CA born between May 2016-April 2017 were enrolled. A total of 1.23% of newborns exhibited CA.…”
Section: Introductionmentioning
confidence: 99%